The Relationship Between the Big Mac Index and Purchasing Power Parity: A Case Study of Colombia (2024)
The relevance of the Big Mac as a proxy indicator for Purchasing Power Parity becomes highly significant during periods of high currency depreciation. Are currencies undervalued or overvalued concerning the dollar? Is absolute and relative purchasing power parity (PPP) observed in Colombia? We address these issues by using a longitudinal data structure and estimating a panel data model. For the Colombian case, there were instances where official reports indicated an appreciation of the peso against the dollar, but the Big Mac index showed a real depreciation. The estimates suggest empirical evidence in favor of absolute PPP, i.e., based on the log-transformed equation estimated using the GLS method, while there is no empirical evidence in favor of meeting PPP in relative terms.